THE EFFECT OF THE MENSTRUAL CYCLE PHASE ON THE OUTCOME OF AUGMENTATION MAMMOPLASTY - T.R. FAYZULLIN (Avicenna Tajik State Medical University, 2021)
Objective: To determine the optimal timing for augmentation mammoplasty (AM) relative to the menstrual cycle phase. Methods: The results of 49 cases of AM performed at different phases of the menstrual cycle were analyzed. The study period was 1 year. The patients were divided into 4 groups depending on the phase of the menstrual cycle: follicular phase during menstruation, follicular phase after menstruation; ovulation; luteal phase. The results were reviewed for intra- and postoperative complications. Results: Patients operated during different phases of menstrual cycle showed significantly different rate of intra- and postoperative complications, such as implant cavity drainage, early hematomas, increased tissue edema and prolonged rehabilitation. Luteal phase of the menstrual cycle was shown to be more favorable for AM with lower risk of complications in the early postoperative period. Conclusion: During planning of AM the phase of menstrual cycle should be considered to reduce the risk of intra- and postoperative complications and provide better outcome of AM.